Gamma Radiation Processed Polymeric Materials for High Performance Applications: A Review - Naikwadi, Amol Tarachand; Sharma, Bhuwanesh Kumar; Bhatt, Keyur D.; Mahanwar, Prakash A. (Frontiers in Chemistry, 2022)
The polymeric properties are tailored and enhanced by high energy radiation processing, which is an effective technique to tune the physical, chemical, thermal, surface, and structural properties of the various thermoplastic and elastomeric polymeric components. The gamma and electron beam radiation are the most frequent radiation techniques used for crosslinking, compatibilizing, and grafting of various polymer blends and composites systems. The gamma radiation-induced grafting and crosslinking are the effective, rapid, clean, user-friendly, and well-controlled techniques for the polymeric materials for their properties improvement for high performance applications such as nuclear, automobile, electrical insulation, construction, medical, and health-care in a different environment. Similarly, electron beam radiations crosslinking has been a well-known technique for properties development and has economic benefits over chemical crosslinking techniques. This review focuses on the development of polymeric multi component systems (functionalized polymer, blends, and nanohybrids), where partially nanoscale clay incorporation can achieve the desired properties, and partially by controlled high energy radiations crosslinking of blends and nanocomposites. In this review, various investigations have been studied on the development and modifications of polymeric systems, such as controlled dose gamma radiations to prepare the clay-induced polymer blends and composites. Radiation induced grafting of the various monomers onto the polymer backbone has been focused. Similarly, comparative studies of gamma and electron beam radiation and their effect on crosslinking and grafting have been focused. The high energy radiation modified polymers have been used in several high performance sectors, including automotive, medical, and electrical insulation applications.